English Teacher Competence in Application Curriculum 2013: Scientific Approach in EFL Teaching - Irfun, Irfun (Global Education Journal, 2024)
Many curricula have been applied in Indonesia, and all have been successfully applied in Indonesian education. In 2013, the Government put the 2013 Curriculum into effect in Indonesia. Before the 2013 Curriculum, the Government applied a Curriculum directed to knowledge, and Teachers had to be active in teaching students; this method has long been applied in Indonesia; it's A unit-level Curriculum, or we usually say it KTSP. This research assesses English teachers' competence in applying the Curriculum 2013, specifically focusing on the Scientific Approach to teaching English as a Foreign Language (EFL). This research uses a systematic literature review (SLR) method. The process will begin with formulating specific research questions and establishing inclusion and exclusion criteria to guide the selection of relevant studies. Based on the research result, some teachers found difficulties in applying the steps/phases of the scientific approach because of limited time, and students' English proficiency could be better could be better. From this research, some urgent strengths and areas need to be improved in implementing the 2013 Curriculum and integrating the Scientific Approach in EFL teaching. Although English teachers demonstrate a strong understanding of the aims of the curriculum, there needs to be more in their competency regarding the effective implementation of the Scientific Approach.